Research Methods and Reporting Practices in Organization Development: A Review and Some Guidelines - Nicholas, John M.; Katz, Marsha (Academy of Management Review, 1985)
John M. Nicholas, Marsha Katz, Research Methods and Reporting Practices in Organization Development: A Review and Some Guidelines, The Academy of Management Review, Vol. 10, No. 4 (Oct., 1985), pp. 737-749